A contribution to the study of architecture of the monastery church of St. Archangel Michael in Prilep - Korunovski Sasho (Zograf, 2011)
The paper deals with architecture of the one of the most significant churches in the Prilep region that was built in the years around 1280 as a foundation of John, the megas chartoularious of the West. The main focus is on the typological concept of the church, and its’ unique combination of a two-domed and two-storeyed structure. In the survey the particular elements of the church structure are elaborated with a reference to the most striking structures that bear such elements in the architecture of the Byzantine sphere of influence.